Penerapan Pendekatan Behavioral dan Kognitif Sosial Dalam Proses Pembelajaran Pendidikan Agama Islam - Mindani Mindani; Rini Puspitasari; Ikhrom Norvaizi; Sulistri Sulistri; Ririn Rizki Apdasuli; Lonie Anggita; Desika Handayani (LP3M IAI Al Urwatul Wutsqo Jombang, 2025)
Most teachers still apply conventional lecture methods and do not utilize positive behavioral reinforcement techniques or interactive social learning models in Islamic Religious Education learning, so that students' critical thinking skills and ability to connect religious teachings with the context of everyday life are underdeveloped. Recent research shows that these two approaches complement each other in creating an effective and adaptive learning process to the needs of today's students. To see and understand it, by using a qualitative approach, namely descriptive research with a focus on analysis, the author conducted a study. This study uses a literature review as its approach. By reading, recording, analyzing, and utilizing library data collection methods. After being collected, the data is analyzed using a methodology that begins with data reduction, data presentation, and drawing conclusions or verification. Both of these approaches have an influence on learning and behavior. However, while behaviorism emphasizes the importance of reinforcement and punishment from the external environment, social cognitive theory emphasizes how individuals actively process and assess information received from their environment. These behavioristic and social cognitive approaches complement each other in Islamic Religious Education learning. The behavioral approach helps understand how behavior can be shaped through external stimuli, while the social cognitive approach explains how internal factors such as thoughts, emotions, and social experiences influence behavior.